2014
DOI: 10.17499/jsser.20331
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bilgiler Dersinde Dijital Vatandaşlığa Dayalı Etkinliklerin Öğrencilerin Dijital Vatandaşlık Tutumlarına Etkisi ve Dijital Vatandaşlık Anlayışlarına Yansımaları-The Effects of Activities for Digital Citizenship on Students' Attitudes toward Digital

Abstract: Anahtar Kelimeler: Dijital vatandaşlık, Sosyal bilgiler dersi, Vatandaşlık eğitimi Extended AbstractProblem: Advances in info-communication technologies have brought many social, cultural, and economic changes along across the world. Recent reflections of these changes over citizenship studies are noteworthy.One of the relevant concepts, digital citizenship can be defined as applying and advocating behaviors necessary for legal, ethical, safe, and responsible use of info-communication technologies in online se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 4 publications
2
18
0
7
Order By: Relevance
“…Moreover, the digital ethics process will be accelerated through the regulations on intellectual and industrial rights (Karaman et al, 2009). When the literature is reviewed, it is seen that the researches carried out by Prensky (2001), Ribble, Bailey, Ross (2004), Mossberger, Tolbert, and Mc Neal (2007) Eid and Ward (2009), Çarıkçı (2010), Ribble (2011), Kocadağ (2012), Ohler (2012), Çubukcu and Bayzan (2013), İşman and Güngören, Ö. C. (2014), Karaduman and Öztürk (2014), Choi (2016), Karaduman, Köse and Eryılmaz (2017), Ünal Dilşat, P. (2017), Çakmak and Aslan (2018), Dere and Yavuzay (2019), Yalçınkaya and Cibaroğlu, M. O. (2019) and Aygun and Ilhan (2020) are the studies covering digital citizenship and its sub-dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the digital ethics process will be accelerated through the regulations on intellectual and industrial rights (Karaman et al, 2009). When the literature is reviewed, it is seen that the researches carried out by Prensky (2001), Ribble, Bailey, Ross (2004), Mossberger, Tolbert, and Mc Neal (2007) Eid and Ward (2009), Çarıkçı (2010), Ribble (2011), Kocadağ (2012), Ohler (2012), Çubukcu and Bayzan (2013), İşman and Güngören, Ö. C. (2014), Karaduman and Öztürk (2014), Choi (2016), Karaduman, Köse and Eryılmaz (2017), Ünal Dilşat, P. (2017), Çakmak and Aslan (2018), Dere and Yavuzay (2019), Yalçınkaya and Cibaroğlu, M. O. (2019) and Aygun and Ilhan (2020) are the studies covering digital citizenship and its sub-dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding student activities, another study looked at the effect of digital citizenship education in the 6 th grade Social Sciences course on students' behaviors in digital platforms and on their learning. The scale that was designed for the purpose of this study demonstrated that the training in digital citizenship had positive effects on students' attitudes towards digital ethics, responsibility, rights, communication, privacy, security and access (Karaduman & Öztürk, 2014).…”
Section: Limitation Report On Theoretical and Conceptual Perspectivesmentioning
confidence: 92%
“…These developments enable people located in various places to reach information and to communicate with one another (Çubukçu & Bayzan, 2013). Thanks to technological advancements, people do not only make use of the information they need but also make themselves available to others by creating and sharing content (Karaduman & Öztürk, 2014). Yet, this eventually causes individuals to develop an addiction to technology.…”
Section: Introductionmentioning
confidence: 99%
“…Digital citizenship is not just the awareness of the risks that can be encountered in digital environments and being protected against these risks. Digital citizens are expected to use digital technologies in a responsible manner (Karaduman and Ozturk, 2014). This situation creates the concept of digital law, which is defined as the awareness of the responsibilities in behaviors and actions in digital environments (Ribble, 2011).…”
Section: Behaviors Sourcementioning
confidence: 99%